Biological Characteristics of Fluorescent Superparamagnetic Iron Oxide Labeled Human Dental Pulp Stem Cells - Liang Ma; Ming-wei Li; Yu Bai; Hui-hui Guo; Sheng-chao Wang; Qing Yu (Stem Cells International)
Tracking transplanted stem cells is necessary to clarify cellular properties and improve transplantation success. In this study, we investigate the effects of fluorescent superparamagnetic iron oxide particles (SPIO) (Molday ION Rhodamine-B™, MIRB) on biological properties of human dental pulp stem cells (hDPSCs) and monitor hDPSCs in vitro and in vivo using magnetic resonance imaging (MRI). Morphological analysis showed that intracellular MIRB particles were distributed in the cytoplasm surrounding the nuclei of hDPSCs. 12.5–100 μg/mL MIRB all resulted in 100% labeling efficiency. MTT showed that 12.5–50 μg/mL MIRB could promote cell proliferation and MIRB over 100 μg/mL exhibited toxic effect on hDPSCs. In vitro MRI showed that 1 × 106 cells labeled with various concentrations of MIRB (12.5–100 μg/mL) could be visualized. In vivo MRI showed that transplanted cells could be clearly visualized up to 60 days after transplantation. These results suggest that 12.5–50 μg/mL MIRB is a safe range for labeling hDPSCs. MIRB labeled hDPSCs cell can be visualized by MRI in vitro and in vivo. These data demonstrate that MIRB is a promising candidate for hDPSCs tracking in hDPSCs based dental pulp regeneration therapy.